2008
DOI: 10.1016/j.jdeveco.2007.06.005
|View full text |Cite
|
Sign up to set email alerts
|

CPI bias and real living standards in Russia during the transition

Abstract: The economies of the former Soviet Bloc experienced large declines in output during the decade of transition which began with the collapse of the Soviet Union in 1991. Yet there are many reasons to believe that measured output and official deflators provide a poor proxy for the change in real living standards in transition economies. This paper uses the Engel curve methodology developed by Hamilton [Hamilton, B. 2001. "Using Engel's Law to Estimate CPI Bias" American Economic Review 91 (3): 619-630] to examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 25 publications
(33 reference statements)
1
30
0
Order By: Relevance
“…During the WMS consumption data was collected for broad (aggregated) categories: 79 food (7 day recall) and 48 non-food items compared with the use of more detailed categories during the KIHBS: 140 food items (7 day recall) and 184 non-food items (1 month recall). 20 Gibson et al [15] also find that subjective wellbeing indicated a much milder decline in living standards between 1994 and 2001 than official estimates had suggested. …”
Section: Poverty Predictions In the Face Of Uncertain Inflation Adjusmentioning
confidence: 94%
See 3 more Smart Citations
“…During the WMS consumption data was collected for broad (aggregated) categories: 79 food (7 day recall) and 48 non-food items compared with the use of more detailed categories during the KIHBS: 140 food items (7 day recall) and 184 non-food items (1 month recall). 20 Gibson et al [15] also find that subjective wellbeing indicated a much milder decline in living standards between 1994 and 2001 than official estimates had suggested. …”
Section: Poverty Predictions In the Face Of Uncertain Inflation Adjusmentioning
confidence: 94%
“…14 Only the estimated parameters of the consumption variance equation are assumed to be stable over time, while the consumption variance predictors are allowed to change. 15 stagnation, increase) and sample size. Classified by the direction of poverty change and the geographic area, a total of 25 different settings can be considered.…”
Section: Assessing the Performance Of Sae Poverty Predictionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet another reason for investigating spatial differences in price movements in Australia is contained in the results of Gibson et al . () for Russia and Barrett and Brzozowski () for Australia. Using the Engel curve‐based methodology, proposed by Hamilton () and Costa (), these studies showed that the conventional consumer price index (CPI) measure will provide biased estimates of price movements.…”
Section: Introductionmentioning
confidence: 99%